Analysis of a T-cell receptor V beta segment implicated in susceptibility to rheumatoid arthritis: V beta 2 germline polymorphism does not encode susceptibility. Issue 12 (December 1993) - Pile, K; Wordsworth, P; Lioté, F; Bardin, T; Bell, J; Cornélis, F
Abstract : OBJECTIVES–The assessment of allelic polymorphism of the T cell receptor gene segment, TCRBV2S1, in rheumatoid arthritis. METHODS–A total of 136 patients with rheumatoid arthritis (RA) (ACR criteria) and 150 controls were TCRBV2S1 genotyped using a nested PCR amplification strategy followed by single-strand conformation polymorphism (SSCP) analysis. RESULTS–The SSCP typing method detected two previously unknown alleles of the TCRBV2S1 gene segment. The TCRBV2S1 allele, genotype and inferred phenotype frequencies were similar in the RA patients and controls. No differences were apparent after the RA patients had been partitioned according to their HLA-DR genotypes. CONCLUSIONS–SSCP analysis is a rapid and efficient method of typing T cell receptor germline polymorphisms. Allelic polymorphism of the T cell receptor variable segment, TCRBV2S1, does not influence susceptibility to RA.